The Roles of Glycans in Bladder Cancer - Jian, Yuli; Xu, Zhongyang; Xu, Chunyan; Zhang, Lin; Sun, Xiaoxin; Yang, Deyong; Wang, Shujing (Frontiers in Oncology, 2020)
Bladder cancer is one of the most common malignant tumors of the urogenital system with high morbidity and mortality worldwide. Early diagnosis and personalized treatment are the keys to successful bladder cancer treatment. Due to high postoperative recurrence rates and poor prognosis, it is urgent to find suitable therapeutic targets and biomarkers. Glycans are one of the four biological macromolecules in the cells of an organism, along with proteins, nucleic acids and lipids. Glycans play important roles in nascent peptide chain folding, protein processing and translation, cell-to-cell adhesion, receptor-ligand recognition and binding and cell signaling. Glycans are mainly divided into N-glycans, O-glycans, proteoglycans and glycosphingolipids. The focus of this review is the discussion of glycans related to bladder cancer. Additionally, this review also addresses the clinical value of glycans in the diagnosis and treatment of bladder cancer. Abnormal glycans are likely to be potential biomarkers for bladder cancer.